Remarks at the Summit on Financing African Economies - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the World Bank Group using all possible resources, financing tools, and dedicated staff across the continent to improve African lives and business prospects. He mentioned the Board-approved financing operations in many African countries to obtain safe doses and to administer them quickly and fairly as soon as the producer countries, COVAX, or manufacturers are ready. Over the past decade, the World Bank Group has invested two hundred billion dollars in Africa. Over the next five years, the Group intends to invest and mobilize another one hundred fifty billion dollars to support the continent’s development. He focused on the need for large inflows of long-term resources for Africa. Another important part of Bank's support to Africa will be mobilization of the private sector, either directly through IFC and MIGA, or indirectly through funding by IDA and IBRD on capital markets. He concluded by highlighting the initiatives for Africa that he discussed with the President Macron recently.